Sukuk Sebagai Alternatif Investasi Syari’ah di Indonesia - Desi Trisnawati (Justicia Islamica, 2011)
Sukuk was one of the alternatives of investment and sources of development fund primarly in infrastructure because of the advantages of the sukuk self namely : (1) the used of sukuk fund from the beginning was clearly to developing certainty projects example infrastructure development in Indonesia, (2) sukuk risks was clearly from the beginning of the projects, and (3) the used of sukuk fund should be discipline because sukuk fund was clearly correlated with certainty projects. The development of sukuk in Indonesia was slowly because of regulation aspect, tax aspect, operational aspect, and product aspect. These factors became the challanges for the Indonesian government to solve immediately in order to sukuk was one of the attractives investment in Indonesia.